Measuring the Return on Investment on Green Projects and Sustainability Efforts. Issue 4 (2nd April 2013) - Phillips, Jack; Phillips, Patti
Abstract This article explains how following a step‐by‐step process and finding the return on investment of green projects and sustainability initiatives will prove to executives, government officials, community leaders, and others involved with the environmental movement that the ultimate payoff is positively substantial. By explaining to readers how to implement the ROI Methodology into these projects and initiatives, this article details how to prove the benefits of green efforts, which include climate control, deforestation, food and hunger, and many other issues we face.